(untitled) (Sains Humanika, 2020)
This study was conducted for the purpose of developing an inventory which assess the implementation of constructive alignment in the teaching and learning system at the Teacher Education Institute (TEI). In this literature analysis, several concepts related to learning outcomes, teaching activities and assessment were discussed. This literature analysis also described in detail the concept of constructive alignment based on few theories and models. Besides, it was also supported by previous studies, assignments and assessments, syllabus, number of hours of student learning, factors that influenced the implementation of constructive alignment, assessment concepts, reliability, the validity and theory of measurement used as a guide and reference in the study. The development of the inventory was carried out in accordance with a basic procedure that involved 11 steps and it was divided into 3 stages, namely the actual stage of inventory development, validation and actual study. During the development stage of the inventory, the researcher divided it into 4 steps: conducting literature review, interviewing expert panels, conducting meta-analysis and producing items. Meanwhile, during the inventory validation stage, the researcher divided it into 5 steps: expert panel judgment, item review, pilot study, data analysis (reliability and validity) and final step of item review and final formatting. Then, at the actual study stage, 2 steps have been identified by conducting research on selected TEIs and analysing the data. This inventory will be used to build a profile of knowledge and practice of constructive alignment among lecturers of Teacher Education Institutes as well as a source of reference in strengthening the assessment system and teaching activities at the TEI in order to maintain the MQA Malaysian accreditation standards that require the assessment system to be based on learning outcomes (Malaysian Qualifications Agency (MQA), 2010). In addition, it is also a source of information for TEI in building the inventory to enhance the level of implementation of constructive alignment. Thus, it will help TEI in grasping the inspiration of the first shift of Malaysia Education Blueprint or PPPM in producing holistic, entrepreneur and balanced graduates.